Intensidade-duração-frequência de precipitação máxima em Mato Grosso - Sabino, Marlus (2018)
This paper aims to obtain the Intensity-Duration-Frequency (IDF) equations of maximum rainfall for 14 rainfall stations in the State of Mato Grosso, belonging to the national hydrometeorological network. The daily pluviograms of each station were digitized and, later, the annual maximum rainfall intensity series were determined with a duration of 10 to 1440 min. From the annual series, 33 probability distribution models were tested by the Kolmogorov-Smirnov test at a 20% significance level to verify the best representation of maximum rainfall intensities in the State. By means of the best fit distribution, the probable maximum rains were calculated with durations varying from 10 to 1440 min, considering the return times of 2, 5, 10, 20, 30, 50 and 100 years. The performance of the IDF equations in estimating the maximum precipitation intensity was with the Mean Square Error (MAE), Mean Square Error Root (RSME), Bias, Willmott's Concordance Index (d), and the Nash-Sutcliffe Efficiency Index (ENS). The distribution with better adhesion to the rainfall stations of Mato Grosso, in different rainfall durations, was the Generalized of Extreme Values (GEV). Rainfall IDF equations were adjusted for each rainy season for a duration of 10 to 360 min due to the low frequency of rainfall with a longer duration. It was observed a great variation in the maximum rainfall intensity and the adjusted parameters of the IDF equation between the stations studied. The good performance of the statistical models, as attested by the empirical statistics, allows the use of IDF equations adjusted for the durations of 10 to 360 min and return time of 2, 5, 10, 20, 30, 50 and 100 years in the regions of the pluviographic stations of the State of Mato Grosso.